Large-scale isolation and purification of yolk immunoglobulin with different purity levels via a combination technique based on high-speed-shear crossflow membrane separation. (July 2023) - Xia, Minquan; Liu, Cong; Ahn, Dong Uk; Huang, Xi; Jin, Yongguo; Cai, Zhaoxia
Abstract: Yolk immunoglobulin (IgY) is an excellent complement or substitute for mammalian immune globulin G, whose development is severely limited for its difficult isolation and purification. This work provides a combination technique for the large-scale isolation of IgY products with different purity levels to meet the market demand. Four levels (IgY-I to IgY-IV) of IgY products were sequentially separated and purified using water dilution, high-speed-shear crossflow membrane separation, and two-step salting out methods, during which the key limiting factors were optimized through the single factor tests. The IgY-I, with purity and yield of 30.69% and 25.06 mg/mL yolk, met the general demand for immune-fortified food for pets. IgY-II and IgY-III achieved purity of 35.84% and 66.09%, yielding 21.76 and 13.92 mg/mL yolk, respectively. Notably, the purity (96.9%) and yield (6.06 mg/mL yolk) of IgY-IV approximated or even exceeded the level of IgY isolated by IgY purification kits, and its purity was higher than that of the commercially available IgY standards. During the isolation, traditional centrifugation and filtration were replaced by continuous flow centrifugation and high-speed-shear crossflow membrane separation for continuous sample loading and sample concentration (a concentration factor of 85.37%). This is of great significance to shortening processing time, saving costs, and meeting needs of large-scale production. This technique has the advantages of high efficiency, low energy consumption, low cost, environmentally friendly, and friendly to human health by supplying IgY products with different purity levels to meet the market demands and promote the development of IgY-related industries. Graphical abstract: Image 1 Highlights: A method was developed for large-scale isolation of yolk immunoglobulin (IgY). A batch of yolks (5 L) were processed continuously to obtain 4 levels of IgY. Level II IgY achieves purity of 35.84%, yield of 21.76 mg/(mL yolk). Level III IgY achieves purity of 66.09%, yield of 13.92 mg/(mL yolk). Purity (96.9%) of level IV IgY higher than that of the available IgY standard.